2021
DOI: 10.1007/s11695-020-05189-6
|View full text |Cite|
|
Sign up to set email alerts
|

Laparoscopic Sleeve-Fundoplication for Morbidly Obese Patients with Gastroesophageal Reflux: Systematic Review and Meta-analysis

Abstract: Introduction Laparoscopic sleeve gastrectomy (LSG) has rapidly become popular with excellent results. However, LSG may exacerbate or increase the risk of “de novo” gastroesophageal reflux disease (GERD). Adding a fundoplication has been proposed to increase the lower esophageal sphincter competency. The aim of this study was to examine the current evidence and outcomes of sleeve-fundoplication (Sleeve-F). Materials and Methods Systematic review and meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
0
9
0
3
Order By: Relevance
“…In a metaanalysis, Oor et al (20) reviewed 33 studies, of which 30 studies reported the effect of LSG on the prevalence of GERD symptoms, 12 reported a decrease in the postoperative prevalence of GERD symptoms, and a total of 24 studies reported the incidence of new-onset GERD symptoms, The incidence of de novo GERD following LSG can be up to 35% and new-onset esophagitis ranged from 6.3% to 63.3%.These series have raised significant concern and debate around the effect of LSG on GERD. The contributive factors to GERD include a decrease in low esophageal sphincter(LES) pressure ( 21), esophageal motility dysfunction, injury to the anti-reflux barrier (disruption of the angle of His and division of sling fibers) (22), increased number of transient LES relaxations, reduction in the compliance of the gastric (5), and increased gastric pressure (23). There are still concerns regarding the real effects of LSG on GERD, while Rouxen-Y gastric bypass has demonstrated a postoperative reduction of GERD.…”
Section: Discussionmentioning
confidence: 99%
“…In a metaanalysis, Oor et al (20) reviewed 33 studies, of which 30 studies reported the effect of LSG on the prevalence of GERD symptoms, 12 reported a decrease in the postoperative prevalence of GERD symptoms, and a total of 24 studies reported the incidence of new-onset GERD symptoms, The incidence of de novo GERD following LSG can be up to 35% and new-onset esophagitis ranged from 6.3% to 63.3%.These series have raised significant concern and debate around the effect of LSG on GERD. The contributive factors to GERD include a decrease in low esophageal sphincter(LES) pressure ( 21), esophageal motility dysfunction, injury to the anti-reflux barrier (disruption of the angle of His and division of sling fibers) (22), increased number of transient LES relaxations, reduction in the compliance of the gastric (5), and increased gastric pressure (23). There are still concerns regarding the real effects of LSG on GERD, while Rouxen-Y gastric bypass has demonstrated a postoperative reduction of GERD.…”
Section: Discussionmentioning
confidence: 99%
“…In 12.7% of all patients, the 24-hour pH monitoring was positive although they did not have GORD 37. Therefore, the Montreal definition is used for inclusion, as it is a non-invasive and globally well-accepted consensus to define GORD 12 13 34 36 38. To objectify and quantify GORD, we will use the validated GORD-Q questionnaire and endoscopy at baseline and during FU 19 39.…”
Section: Discussionmentioning
confidence: 99%
“…More studies are needed to determine the ideal surgical technique for such patients predisposed to GERD and EE after LSG. Initial results for concomitant LSGfundoplication were associated with increased complication rates [27]. The authors also eagerly await the results of the RELIEF trial, which investigated the role of LINX TM magnetic sphincter augmentation in patients with postoperative GERD after LSG, that has recently nished recruitment (ClinicaTrials.gov Identifer: NCT02429830).…”
Section: Discussionmentioning
confidence: 99%